Taxonomic status of Parotia berlepschi Kleinschmidt, 1897 based on analysis of external appearance, voice and behavior (Aves: Paradisaeidae) - Scholes, Edwin; Beehler, Bruce M.; Laman, Timothy G. (Zootaxa, 2017)
Described from trade-skins of unknown origins, Parotia berlepschi Kleinschmidt, 1897 was the subject of a longstanding ornithological mystery that remained unresolved for well over a century. With few specimens and no known wild population, most taxonomic assessments over the last century have treated P. berlepschi as a subspecies of Parotia carolae Meyer, 1894. Following discovery of its geographical home in 2005, most authorities returned to giving P. berlepschi full species status. However, evidence supporting the delineation of P. berlepschi from P. carolae has not yet been fully articulated in the literature. Here, we assess phenotypic differentiation and the taxonomic status of P. berlepschi relative to P. carolae based on specimens and recordings of wild birds. With regard to external appearance and voice, which are important intersexual signals among polygynous birds-of-paradise, our analysis confirms that P. berlepschi is well-differentiated from P. carolae and should be treated as specifically distinct. Evidence for differentiation in courtship behavior is inconclusive and requires further study.